AN ANALYSIS ON DEIXIS IN THE SONG LYRICS OF JUSTIN BIEBER’S “MY WORLD” ALBUM - Ratri Yuliningrum; Zulfa Afis Sunani; Anginna Birochmatika (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
This study aimed to analyze the type of deixis in the song lyrics of Justin Bieber's "My World" Album. There were seven (7) song lyrics in this album, analyzed using a pragmatic approach of the theory Alan Cruse. The method used in this study was descriptive qualitative. The deixis analysis in this study focused on person deixis, spatial deixis, and temporal deixis. The result of this study found 800 person deixis, 197 spatial deixis, and 82 temporal deixis in this album.